Of goblins and gods: 3,500 years of cobalt and its pigments - (:unkn) unknown (Leuven University Press, 2026)
Cobalt: named after goblins, allotted to gods. Cobalt and its compounds have had a long and important part to play in history. Metallic cobalt is a modern innovation, vital in the green energy transition. However, cobalt compounds have been used for 3,500 years to create deep-blue pigments, featuring in many important works of art and religious artefacts, associated with heaven, eternity and the divine. Cobalt ores are rare, and their exploitation is a dangerous pursuit. Their co-occurrence with arsenic has led to severe health consequences for workers, which were blamed on supernatural spirits and goblins, “kobolds”, from which the name cobalt is derived. Of Goblins and Gods discusses the state-of-the-art extraction and use of cobalt ores through history, alongside the technology involved in making and applying cobalt pigments in many man-made materials across all regions and periods, from the Death Mask of Tutankhamun and pre-Islamic tiles to Indian manuscripts and the windows of Canterbury Cathedral.